The Anti-Viral and Cognitive Enhancement Properties of Edible Bird's Nest: A Narrative Review - Yusnianingsih, Cuay (PT BMW Journal Sejahtera, 2024)
Background: Edible bird's nest has been used as a traditional Chinese medicine since the 7th century. It is rich in protein, carbohydrates, moisture, ash, and fat. Recent research has focused on its potential health benefits, such as anti-viral properties, cognitive enhancement, and roles as an immunomodulator and antioxidant. Objective: This review explores the anti-viral and cognitive enhancement properties of edible bird's nest. Methods: This review followed the PRISMA Scoping Review (PRISMA ScR) guidelines. Relevant studies were systematically identified using PubMed and Google Scholar with keywords such as